Kajian Pemberian Macam Bahan Organik terhadap Aktivitas Pengikatan Al, Fe dan Serapan P Jagung Manis (Zea mays saccharata Strurt) Pada Andisol Tawangmangu - Sri Hartati; Hery Widijanto; Ana Yulia Fitriyanti (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2012)
Tittle : Study The Kinds of Organic Matter On Activity Of Al, Fe and P Uptake by Sweet Corn (Zea mays saccharata Sturt) In Andisol Tawangmangu. This research aimed to find out the effect of organic matters on activity of Al, Fe and the P uptake by sweet corn in Andisol Tawangmangu . This research was conducted on July until Desember 2005 in Green House. Soil chemistry analysies was conducted at Chemistry and Soil Fertility laboratory in Agricultural Faculty of Sebelas Maret University, Surakarta. The research used factorial design experiment with completely randomized design with two factors. First factor was kind of organic matters (B), which contains of 4 kinds  there were Bo (no organic matter), B1 (cattle manure, 14.25 ton Ha-1 or 71.25 g/polibag), B2 (Gliricidia sepium, 10 ton Ha-1 or 50 g/polibag), B3( rice strow, 12 ton Ha-1 or 60 gr/polibag). The second factor was plant periode ( I ) devided at 6 level there are Io (0 days), I1 ( 10 days), I2 ( 20 days), I3 ( 40 days), I4 (60 days), I5 (90 days). Data analyzed used Variance Analysis, to know the influence of treatment and continued by DMRT to  comparing inter treatment. And  to find the relation between among treatment data analyzed by correlation test. The result of research showed that organic matters significant to reduce activity of Al, Fe and increase P uptake by sweet corn. Treatment with  Gliricidia sepium  reduce Al-oksalat and Fe-oksalat higher than cattle manure and rice strow that are 31.07 % and 36.53 % to control. Decrease of Al and Fe could increase P uptake of sweet corn 0.82 g  plant-1.